Optimization of Microbial Process for the Conversion of Kitchen Waste into Organic Acids Using Response Surface Methodology - Hafid, Halimatun Saadiah (2011)
Model kitchen waste was formulated in this study to overcome the problem of kitchen waste variation composition. The performance of organic acids production was compared between the model kitchen waste and actual kitchen waste. Both substrates were subjected to anaerobic treatment by indigenous mixed microflora from fermented kitchen waste in a 250 mL shake flask. The parameters conditions used were agitation at 200 rpm, adjusted pH 5 and 7 and temperature of 30°C, 37°C and 40°C. The highest organic acid produced in real kitchen waste and model kitchen waste were 48.64 g/L and 37.49 g/L, respectively after 6 days of incubation at pH 5 and 37°C. For both kitchen waste fermentation, lactic acid was dominant (76.2%) followed by acetic acid (17.7%) and butyric acid (6.1%). Organic acids production from model kitchen waste fermentation was further improved by optimization of fermentation procedures using response surface methodology (RSM). Central composite design (CCD) was employed to determine the maximum organic acids production for several parameter variables which include temperature, pH adjusted intermittently and inoculum size. The source of inoculum was originated from kitchen waste being used after 15 days of fermentation. The optimum temperature, pH and inoculums size for the acidogenic fermentation of organic acids from kitchen waste were 35C, adjusted pH 6.0 and 20%, respectively. The predicted value for the final organic acids produced in this optimal fermentation was 78.20 g/L. The verification study has been carried out and the maximum organic acid produced was 77.28 g/L. Organic acids production was significantly affected by pH and temperature and the interaction between them. Lactic acid showed the main organic acids detected in the kitchen waste fermentation (more than 80%) followed by acetic acid and butyric acid. The organic acids produced have potential to be used as substrate for the production of biopolymer.